Evaluation of SICAP pre-employment supports - Delaney, Judith; Seamus, McGuinness; Emer, Smyth; Adele, Whelan (ESRI, 2020)
ESRI research shows improved employment outcomes among the long-term unemployed who receive employment supports under the Social Inclusion and Community Activation Programme (SICAP).